Pasteur : premier des post-pasteuriens ? - Marine de Guglielmo (Revue d'anthropologie des connaissances)
This article aims to discuss the historical and anthropological divide theorized by contemporary authors Heather Paxson and Jamie Lorimer, between the “Pasteurian” era and the “post-Pasteurian” era or between the “antibiotic” era and the “probiotic” era. We thus propound a reinterpretation of the work of Pasteur and his collaborators, in order to question the antagonism which would oppose them to contemporary “post-pasteurism”.